2015
DOI: 10.5423/ppj.oa.07.2014.0064
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Coupling and Repulsion Phase DNA Marker Associated With an Allele of a Gene Conferring Host Plant Resistance to Pigeonpea sterility mosaic virus (PPSMV) in Pigeonpea (Cajanus cajan L. Millsp.)

Abstract: Pigeonpea Sterility Mosaic Disease (PSMD) is an important foliar disease caused by Pigeonpea sterility mosaic virus (PPSMV) which is transmitted by eriophyid mites (Aceria cajani Channabasavanna). In present study, a F2 mapping population comprising 325 individuals was developed by crossing PSMD susceptible genotype (Gullyal white) and PSMD resistant genotype (BSMR 736). We identified a set of 32 out of 300 short decamer random DNA markers that showed polymorphism between Gullyal white and BSMR 736 parents. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similarly, KSRON 107 and KSRON 109, despite exhibiting slow rusting nature, expressed an MSS reaction to stem rust pathogen. This might be attributed to the presence of high yielding and disease resistance gene(s) being in the repulsion phase rather than coupling [55].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, KSRON 107 and KSRON 109, despite exhibiting slow rusting nature, expressed an MSS reaction to stem rust pathogen. This might be attributed to the presence of high yielding and disease resistance gene(s) being in the repulsion phase rather than coupling [55].…”
Section: Discussionmentioning
confidence: 99%
“…A genetic population of moderate size segregating for the desired trait(s) is essentially needed to find significant associations between the DNA markers and trait(s) under consideration. Experimental populations stemming from a cross between two contrasting genotypes have been developed in pigeonpea targeting several traits such as resistance to important biotic/abiotic factors, fertility restoration, and growth habit/flowering patterns (Varshney et al 2010;Khalekar et al 2014;Daspute and Fakrudin 2015). In parallel, reverse genetic tools like targeted induced local lesions in genomes (TILLING) population derived from EMS-treated 'Asha' were also reported in pigeonpea (Varshney et al 2010).…”
Section: Next-generation Mapping Resourcesmentioning
confidence: 99%
“…Examples of F 2 -based BSA include RAPD markers for FW and plant type (Dhanasekar et al 2010), and AFLP marker for SMD (Ganapathy et al 2009) (see . More recent application of BSA in F 2 population (Gullyal white  BSMR 736) facilitated detection of a repulsive-phase RAPD fragment co-segregating with SMD resistance (Daspute and Fakrudin 2015). Similarly, Khalekar et al (2014) found five SSR markers to be associated with FW resistance by analyzing resistant and susceptible bulks of an F 2 population (ICPL 87119  T. Vishakha-1).…”
Section: Genetic Inheritance and Gene/qtl Discoverymentioning
confidence: 99%
“…A genetic population of moderate size segregating for the desired trait(s) is essentially needed to find significant associations between the DNA markers and trait(s) under consideration. Experimental populations stemming from a cross between two contrasting genotypes have been developed in pigeonpea targeting several traits such as resistance to important biotic/abiotic factors, fertility restoration, and growth habit/flowering patterns Khalekar et al 2014;Pazhamala et al 2015;Daspute and Fakrudin 2015). In parallel, reverse genetic tools like targeted induced local lesions in genomes (TILLING) population derived from EMS-treated 'Asha' were also reported in pigeonpea .…”
Section: Next-generation Mapping Resourcesmentioning
confidence: 99%
“…Examples of F 2 -based BSA include RAPD markers for FW (Kotresh et al 2006) and plant type (Dhanasekar et al 2010), and AFLP marker for SMD (Ganapathy et al 2009) (see Bohra et al 2014). More recent application of BSA in F 2 population (Gullyal white  BSMR 736) facilitated detection of a repulsive-phase RAPD fragment co-segregating with SMD resistance (Daspute and Fakrudin 2015). Similarly, Khalekar et al (2014) found five SSR markers to be associated with FW resistance by analyzing resistant and susceptible bulks of an F 2 population (ICPL 87119  T. Vishakha-1).…”
Section: Genetic Inheritance and Gene/qtl Discoverymentioning
confidence: 99%